Quality Control of Trobos Livestock Magazine Production at PT Aksara Grafika Pratama - Gema Sukmawati Suryadi; Antinah Latif; Alfredo Alfredo (Kreator, 2021)
Quality control is an important factor for the industry because continuously control process in production will be able to detect abnormalities results quickly, so that it can be anticipated immediately. This study aims to determine how the quality control process has been implemented, what printing problems often occur, and what activities have been carried out to control the production quality of Trobos Live Stock magazine at PT Aksara Grafika Pratama. This research method is descriptive with direct observation of the production process at PT Aksara Grafika Pratama. Descriptive method has been used by direct observation of the production process at PT Aksara Grafika Pratama. Data analysis was carried out using the p-chart control chart analysis method of the production quantity and misprint of Trobos Live Stock Magazine in January - December 2019. The results showed that the total production of Trobos Live Stock Magazine by PT Aksara Grafika Pratama in 2019 was 225,521 sheets with 7,178 misprints, and the average proportion of damaged products was 0.030. The proportion of damaged production in April and May occupied the highest position, namely 0.045 and 0.049, exceeding the UCL (Upper Control Limit) control limit. However, in the production process the following month the damage to production is within control limits, which indicates that the production department has carried out the maximum evaluation and repair. Misprints that occur in the production process of Trobos Live Stock Magazine include Scumming, Ghosting, and no images or text appearing in certain parts. Quality control activities carried out by PT Aksara Grafika Pratama to reduce the level of damage to production include implementing a layered system such as directly monitoring the production process, always carrying out maintenance on machines and assigning special experts to repair machines, as well as placing experienced workers to minimize possible error rate during the production process.Keywords — Quality Control, Diagrams Control p-chart, Statistical Assistance Tools